2010
DOI: 10.2533/chimia.2010.793
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of an Enzymatic Method for the Rapid Determination of Gamma Hydroxybutyric Acid

Abstract: Gamma hydroxybutyric acid (GHB) is a regulated therapeutic drug, which naturally occurs in mammalian brain tissues as an intermediate of the GABA (gamma aminobutyric acid) neurotransmitter metabolism. The increasing misuse of GHB as a narcotic or abusing drug in recent years calls for the development of a simple and rapid screening method as an alternative to the currently available, technically demanding diagnostic methods. We have developed a rapid enzymatic assay based on the GHB dehydrogenase of Ralstonia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The increase in absorbance at 340 nm is proportional to GHB concentration. 17 The lower detection limit of the GHB kit is 2 mg/l and the lower limit of quantification is 5 mg/l, according to the information of the manufacturer. The 97.5th percentile in serum of blood donors who did not consume GHB is 6.1 mg/l.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in absorbance at 340 nm is proportional to GHB concentration. 17 The lower detection limit of the GHB kit is 2 mg/l and the lower limit of quantification is 5 mg/l, according to the information of the manufacturer. The 97.5th percentile in serum of blood donors who did not consume GHB is 6.1 mg/l.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Immunologic detection is not appropriate for GHB. 17,18 Thus a suitable clinical chemical detection method is still an obstacle of its widespread availability.…”
Section: Introductionmentioning
confidence: 99%
“…The brain cerebral cortex and hippocampus tissue norepinephrine level measured according to Kapoor and Chalmers (1987) method. The brain cerebral cortex and hippocampus tissue gamma aminobutyric acid (GABA) level evaluated according to Sciotti et al (2010) method.…”
Section: Brain Cerebral Cortex and Hippocampus Neurotransmitters Testsmentioning
confidence: 99%
“…Unfortunately, their reliability was inconclusive and showed different results. 9,16,17 GHB's small nonspecific structural formula makes enzymatic tests prone to cross-reactivity with other similar compounds such as ethanol. 9 Drogies et al 18 reported a novel enzymatic method (Bühlmann Laboratories, Schönenbuch, Switzerland) that was used to measure GHB in serum of 13 patients.…”
Section: Introductionmentioning
confidence: 99%